Impacto do aumento da progesterona endógena pelo uso de hCG sobre os transcritos dos interferons no endométrio e no concepto durante a gestação inicial em bovinos - Manta, Manuela Wolker (2024)
One of the major obstacles to productivity in beef production is pregnancy loss, characterized by embryonic mortality. In cattle, high concentrations of progesterone (P4) soon after conception are associated with improved embryonic development, increased secretion of IFNT, and increased pregnancy rates; one of the tools used to increase P4 concentrations is the use of Human Chorionic Gonadotropin, the hCG. In this context, this thesis has been developed to elucidate the effects of increased endogenous P4, using the tool of hCG administration as an inducer of accessory corpus luteum, in the uterine environment (endometrium) and in the conceptus, during early gestation in cattle. This thesis hypothesizes is that increased circulating P4, in the first days of gestation in cattle, leads to better signaling of maternal recognition of pregnancy, through a uterine environment conducive to embryonic development and concepts with greater signaling capacity. Article 1 described the expression pattern of genes involved in the Interferon Tau (IFNT) pathway and Interferon Stimulated Genes (ISGs) in the endometrium at 18 days of gestation. As a result, we demonstrated that hCG, administered on day 5 after fertilization, increases the concentration of P4 and upregulates the genes involved in the IFNT signaling pathway and ISGs in the endometrium at 18 days of pregnancy. In this first article, the size of the pre-ovulatory follicle on D0, the size of the corpus luteum on D5, the size of the CL on D14, the volume and weight of the CL on D18 did not differ between the Control and hCG groups. The increase in P4 on D14 in the hCG group can be attributed to the greater luteal mass present in this group, since females in the treated group showed a 62.5% rate of formation of accessory CL, increasing the total luteal mass producing P4 (none cows from the Control group showed formation of accessory CL). Regarding gene expression, IFNAR1 and STAT1 and all ISGs evaluated showed higher expression in the hCG group compared to the Control group. The article 2 suggested stimulation in the conceptus based on the results observed in the endometrium; our results showed that the embryos at day 18 did not differ in size or area, either in the expression of ISGs or cell proliferation genes. Based on these results, we suggest that the greatest impact of the increase in serum P4 in the conceptus occurs before the day evaluated in our study, in a more recent period in gestation, and before the peak of IFNT production/expression. When addressed in the endometrium, hCG upregulates IFNT signaling genes and ISGs during early pregnancy and may play an important role in the maternal recognition of pregncnay of IFNT. Regarding the approach in the conceptus, the increase in progesterone-induced by hCG administration did not alter the expression of genes related to IFNT-signaling and embryonic development/proliferation. These data are part of an ongoing research project, therefore further analyses will be performed to fully elucidate the events occurring during this period in bovine concepts under or without the influence of high P4. Understanding the roles of these genes in uterine receptivity and the conceptus during implantation is necessary to develop strategies to increase fertility in ruminants and other species.